Computing vertical profile of temperature in Eastern Sea using cubic spline functions - Pham, Hoang Lam (VNU, 2014)
In this paper the spline approximation was appliedto the empirical vertical profiles of oceanographic parameters such as temperature, salinity or density to obtain a more precise and reliable result of interpolation. Our experiments with the case of observed temperature profiles in Eastern Sea show that the cubic polynomial spline method has a higher reliability and precision in a comparison with the linear interpolation and other traditional methods. The method was realized as a subroutine in our programs for oceanographic data management and manipulation. As an application, the observed temperature field from World Ocean Atlas 2001 consists of about 137000 vertical profiles have been analyzed to examine the features of the vertical distribution of temperature in Eastern Sea. It is found that the upper homogeneous layer in the summer months is only a thin one with the thicknessof about 10m, but in the winter months this layer expands to the depth of about 50-60m and evenmore. The thickness of upper mixing layer changes largely from year to year with a range fromabout 20m to about 70m.